2011
DOI: 10.1111/j.1467-2979.2011.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of habitat and fishing in influencing reef fish communities across seventeen Pacific Island Countries and Territories

Abstract: Reef fish assessments were undertaken in 17 Pacific islands to describe the status of finfish resources in 63 villages where fishing is mainly artisanal. Surveys were performed by recording the number and size of edible fish species and benthic composition. Fishing impact was described through six proxies representing level of catch, alternative incomes, degree of commercial catch and country economic development derived from a simultaneous socioeconomic assessment. The relative importance of broadly defined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 56 publications
6
53
0
Order By: Relevance
“…Hawaiian Islands [79]; Line Islands [80]). Although large-scale patterns in fish community structure are influenced by numerous factors, including historical biogeography, reef geomorphology and human activities unrelated to fishing [81,82], a global metaanalysis of local-scale studies has found a positive relationship between fishing pressure and damselfish abundance that is consistent with the earlier studies [83]. Regardless of the specific mechanism that underlies this relationship, our study indicates that an increase in intensive territorial grazers will be likely to have substantial implications for the structure of the benthic microbial community on coral reefs, potentially increasing reservoirs of opportunistic pathogens linked to coral disease as well as the occurrence of coral disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hawaiian Islands [79]; Line Islands [80]). Although large-scale patterns in fish community structure are influenced by numerous factors, including historical biogeography, reef geomorphology and human activities unrelated to fishing [81,82], a global metaanalysis of local-scale studies has found a positive relationship between fishing pressure and damselfish abundance that is consistent with the earlier studies [83]. Regardless of the specific mechanism that underlies this relationship, our study indicates that an increase in intensive territorial grazers will be likely to have substantial implications for the structure of the benthic microbial community on coral reefs, potentially increasing reservoirs of opportunistic pathogens linked to coral disease as well as the occurrence of coral disease.…”
Section: Discussionmentioning
confidence: 99%
“…The island types considered here can be qualitatively defined by their diversity and relative proportions of various habitats present. The presence, scale and proximity of particular habitats have a strong influence on the diversity and carrying capacity of reef fish assemblages [39,40], and analysis of fish communities on oceanic islands throughout the Pacific reveals predictable structuring of trophic groups based on the island types described here [20]. In particular, Pinca et al [20] found that, after partialling out the effects of fishing, parrotfish density and biomass was positively related to barrier reef systems with lagoons and negatively related to atolls and low complexity fringing reef systems, whereas fringing reefs supported greater mean body sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence, scale and proximity of particular habitats have a strong influence on the diversity and carrying capacity of reef fish assemblages [39,40], and analysis of fish communities on oceanic islands throughout the Pacific reveals predictable structuring of trophic groups based on the island types described here [20]. In particular, Pinca et al [20] found that, after partialling out the effects of fishing, parrotfish density and biomass was positively related to barrier reef systems with lagoons and negatively related to atolls and low complexity fringing reef systems, whereas fringing reefs supported greater mean body sizes. Specific habitats prevalent in wave-protected environments like lagoons provide major nursery habitat for many parrotfishes, including C. spilurus [41,42], and therefore may boost abundance potential for adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing selective fishing pressure contributes to the truncation of age structure (Hsieh et al, 2006) and changes the composition of reef fish communities (Pinca, 2011). The impacts of fisheries can be detected in changing catch rates and catch composition (Welcomme, 1999).…”
Section: Introductionmentioning
confidence: 99%